Micronodular thymic carcinoma with lymphoid hyperplasia: relevance of immunohistochemistry with a small panel of antibodies for diagnosis: a RYTHMIC study - Thomas de Montpréville, Vincent; Mansuet-Lupo, Audrey; Le Naoures, Cécile; Chalabreysse, Lara; De Muret, Anne; Hofman, Véronique; Rouquette, Isabelle; Piton, Nicolas; Dubois, Romain; Benitez, Jose Carlos; Girard, Nicolas; Besse, Benjamin; et al. (Virchows Archiv, 2021)
Micronodular thymic carcinoma with lymphoid hyperplasia (MNTCLH) is a rare form of thymic carcinoma. We present the experience of RYTHMIC, the French national network devoted to the treatment of thymic epithelial tumors through multidisciplinary tumor boards with a review of all tumors by pathologists for classification and staging. Six cases of MNTCLH were diagnosed during a review of 1007 thymic epithelial tumors. Histologically, epithelial cells with atypia and mitoses formed micronodules that were surrounded by an abundant lymphoid background with follicles. There was neither obvious fibro-inflammatory stroma nor necrosis. Spindle cells areas were common. Initial diagnosis was micronodular thymoma in two cases, cellular atypia being overlooked, eclipsed by the micronodular pattern. Immunohistochemistry with a panel of five antibodies showed that cytokeratins (AE1-AE3) and p63-positive epithelial cells also expressed CD5 and that there was no TdT-positive cells within the tumors. CD20 highlighted the lymphoid hyperplasia. Additionally epithelial cells also expressed CD117 and diffusely Glut 1. Twenty-seven micronodular thymomas with lymphoid stroma diagnosed during the same period did not show the CD5 and CD117 positivities seen in MNTCLH and contained TdT-positive lymphocytes. Three of the 6 patients with MNTCLH had adjuvant radiotherapy. Three patients with follow-up information were alive without recurrence at 38, 51, and 95 months. Our study shows that immunohistochemistry, such as that used in the RYTHMIC network with a small panel of antibodies, may easily help to confirm the correct diagnosis of MNTCLH, a rare and low-aggressive form of thymic carcinoma, and avoid the misdiagnosis of micronodular thymoma.